Towards the emerging crosstalk: ERBB family and steroid hormones. (February 2016) - D'Uva, Gabriele; Lauriola, Mattia
Highlights: A mutual crosstalk between growth factors acting through receptor tyrosine kinases (RTKs) of ERBB family and steroid hormones acting through nuclear receptors (NRs) is attained by both genomic and non-genomic interactions. Steroid hormones fine-tune ERBB signalling dynamics and cellular output by modulating feedback regulatory loops. Drug combinations of NR and RTK agonists or antagonists may be a strategy for the development of new therapies in a broad range of diseases, including cancer. Understanding the circadian glucocorticoid regulation of ERBB (and RTK) signalling provides the basis for chronotherapy to improve anti-cancer treatment efficacy. Time-resolved analysis of the global genomic response to steroid hormones and growth factor combinations could lead to major advances in molecular medicine. Abstract: Growth factors acting through receptor tyrosine kinases (RTKs) of ERBB family, along with steroid hormones (SH) acting through nuclear receptors (NRs), are critical signalling mediators of cellular processes. Deregulations of ERBB and steroid hormone receptors are responsible for several diseases, including cancer, thus demonstrating the central role played by both systems. This review will summarize and shed light on an emerging crosstalk between these two important receptor families. How this mutual crosstalk is attained, such as through extensive genomic and non-genomic interactions, will be addressed. In light of recent studies, we will describe how steroid hormones are able to fine-tune ERBB feedback loops, thus impacting on cellular output and providing a new key for understanding the complexity of biological processes in physiological or pathological conditions. In our understanding, the interactions between steroid hormones and RTKs deserve further attention. A system biology approach and advanced technologies for the analysis of RTK-SH crosstalk could lead to major advancements in molecular medicine, providing the basis for new routes of pharmacological intervention in several diseases, including cancer.